Academic Senate Minutes 2006-10-12 - Academic Senate:::::::::
Announcements from the Chair. Report of the Chair. Moment of silence for Rand Link. Approval of Agenda. Approval of minutes of 9/14/06. Update on WASC. Provost Report. Cost Sharing Policy first reading. SPECIAL REPORT: CSU Coded Memorandum: Access to Electronic and Information Technology for Persons with Disabilities. Capping Size of Senate first reading. Associated Student Report. Statewide Senators report. APC report. EPC report. SAC report. SBC report. Good of the Order.